Composite electrode material and preparation method and application thereof
Mesoporous graphite is prepared by etching graphite by potassium manganate, and heat treatment is carried out with titanium alcohol solution to form a titanium nitride cladding layer, which solves the performance attenuation problem caused by volume expansion during charging and lithium embedding, and achieves low Expansion, high lithium ion diffusion capability and good cycling performance.
Patent Information
- Application Number
- CN202411675247.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The volume expansion of existing silicon carbon materials during charging and embedded lithium causes the breakage of active particles, the surface SEI film structure is unstable, and the interface impedance is increased, resulting in rapid attenuation of electrochemical performance and low cycle life.
Mesoporous graphite is prepared by etching graphite by potassium manganate, and a gaseous silicon source is deposited thereon to form a porous silicon-carbon material. Then, a second heat treatment is performed with the titanium source alcohol solution to form a titanium nitride coating layer to prevent the F ions in the electrolyte from passing through and reduce side reactions.
This method significantly improves circulation performance and battery safety by reserving silicon expansion space, reducing material breakage, reducing interface side reactions, and maintaining good lithium ion diffusion capabilities.
Smart Images

Figure BDA0005146844010000121
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a composite electrode material and a preparation method and application thereof. Background Art
[0002] With the rapid development and continuous growth of the new energy vehicle industry, the development of high-power, high-capacity and high-safety battery systems is imminent. Silicon-carbon anode materials have received extensive attention and research due to their high theoretical specific capacity, low lithium insertion potential, abundant raw materials, non-toxicity and environmental protection, and are expected to replace carbon anode materials and become the next generation of high-performance lithium battery anode materials.
[0003] As a semiconductor, silicon has poor conductivity, and the huge volume expansion of silicon-carbon negative electrode materials during the process of lithium insertion and extraction leads to the crushing and pulverization of active particles, and the instability of the surface SEI film structure and continuous growth, which further increases the interface impedance, causing the electrochemical performance of the silicon negative electrode to decay rapidly and the cycle life to be low. Therefore, it is very important to prepare silicon-carbon materials with a stable structure that can accommodate silicon expansion to reduce material crushing during the expansion process and enhance the cycle performance.
[0004] Traditionally, carbon coating is used to coat silicon-carbon materials, but the carbon layer has no selective permeability to the electrolyte, and the internal silicon reacts with the F ions in the electrolyte, resulting in an increase in side reactions. Therefore, it is necessary to develop a new coating layer to prevent the F ions in the electrolyte from passing through and reduce side reactions, while ensuring good conductivity and lithium ion diffusion performance.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One object of the present invention is to provide a method for preparing a composite electrode material to solve the technical problems of electrochemical performance attenuation and low cycle life of existing silicon-carbon materials.
[0007] Another object of the present invention is to provide a composite electrode material having low expansion, high lithium ion diffusion capacity, few interface side reactions and good cycle performance.
[0008] Another object of the present invention is to provide a negative electrode sheet.
[0009] Another object of the present invention is to provide a battery.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] A method for preparing a composite electrode material comprises the following steps:
[0012] The graphite material and potassium manganate are subjected to a first heat treatment to obtain mesoporous graphite, and a gaseous silicon source is deposited on the mesoporous graphite to obtain a porous silicon-carbon material; the mixed system of the porous silicon-carbon material and a titanium source alcohol solution is subjected to a second heat treatment to obtain a composite electrode material.
[0013] In some embodiments, the mass ratio of the graphite material to potassium manganate is 2:(4-7).
[0014] In some embodiments, the temperature of the first heat treatment is 1000-1200° C., and the time of the first heat treatment is 3-6 hours.
[0015] In some embodiments, the mesoporous graphite has a mesoporosity of 50% to 70%.
[0016] In some embodiments, after the first heat treatment, washing and drying are further included to obtain the mesoporous graphite.
[0017] In some embodiments, during the process of depositing the gaseous silicon source on the mesoporous graphite, the deposition temperature is 400-800° C., the deposition time is 1-15 h, the pressure is 0.01-10 Kpa, and the flow rate of the gaseous silicon source is 0.5-2 L / min.
[0018] In some embodiments, the titanium source alcohol solution includes titanium tetrachloride ethanol solution.
[0019] In some implementations, the mass fraction of the titanium source alcohol solution is 8% to 12%.
[0020] In some embodiments, the mass ratio of the titanium source alcohol solution to the porous silicon-carbon material is (2-4):1.
[0021] In some embodiments, the second heat treatment includes preheating and calcining.
[0022] In some implementations, the preheating temperature is 400-550° C., and the preheating time is 1-5 hours.
[0023] In some implementations, the calcination temperature is 1400-1600° C., and the holding time is 3-7 hours.
[0024] In some embodiments, the calcination is performed under protective gas conditions at a pressure of 0.08 to 0.12 MPa.
[0025] A composite electrode material is prepared by the composite electrode material preparation method.
[0026] An electrode sheet comprises the composite electrode material prepared by the composite electrode material preparation method or the composite electrode material.
[0027] A battery comprises the electrode sheet.
[0028] An electrical device comprises the battery.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The preparation method of the composite electrode material of the present invention comprises the following steps: preparing mesoporous graphite with suitable mesoporosity by etching graphite with potassium manganate, thereby reserving space for the expansion of silicon and preventing the material from being broken during the charging and lithium insertion process; and the mesopores are conducive to the diffusion of lithium ions; a titanium source alcohol solution is mixed with a porous silicon-carbon material for coating, and the obtained titanium nitride coating layer can prevent fluoride ions in the electrolyte from passing through the coating layer into the interior of the material for side reactions, and the coating layer has good lithium ion diffusion. Due to the reduction of interface side reactions, the interface impedance does not change much, and the surface of the material still has good lithium ion diffusion capacity after cycling.
[0031] (2) The composite electrode material of the present invention has a core of silicon-carbon material, and the mesoporous graphite reserves space for the expansion of silicon to prevent the material from breaking during the charging and lithium insertion process. At the same time, the appropriate mesoporosity is conducive to the diffusion of lithium ions. The titanium nitride coating layer coated on the surface of the silicon-carbon material can improve the diffusivity of lithium ions, has good conductivity, reduces interface side reactions, and has good cycle stability.
[0032] (3) The battery of the present invention has excellent lithium ion diffusion capacity, low expansion when fully charged, good cycle performance and high safety. DETAILED DESCRIPTION
[0033] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0034] According to one aspect of the present invention, the present invention relates to a method for preparing a composite electrode material, comprising the following steps:
[0035] The graphite material and potassium manganate (K2MnO4) are subjected to a first heat treatment to obtain mesoporous graphite, and a gaseous silicon source is deposited on the mesoporous graphite to obtain a porous silicon-carbon material; the mixed system of the porous silicon-carbon material and a titanium source alcohol solution is subjected to a second heat treatment to obtain a composite electrode material.
[0036] The method of the present invention prepares mesoporous graphite with suitable mesoporosity by etching graphite with potassium manganate, and deposits silicon in the mesopores of the mesoporous graphite. The mesopores reserve space for silicon expansion in advance to prevent the material from breaking during the charging and lithium insertion process. At the same time, the mesopores are conducive to the diffusion of lithium ions. The reaction principle includes: K2MnO4+C→K2CO3+MnO; 2MnO2+C→2MnO+CO2. The titanium source alcohol solution is mixed and coated with the porous silicon-carbon material. The titanium nitride (TiN) coating layer obtained by carbon thermal reduction nitridation technology can prevent fluoride ions in the electrolyte from passing through the coating layer into the interior of the material and undergoing side reactions. At the same time, the coating layer has good lithium ion diffusion. Due to the reduction of interface side reactions, the interface impedance does not change much, and the material surface still has good lithium ion diffusion capacity after cycling.
[0037] In some embodiments, the mass ratio of the graphite material to potassium manganate is 2:(4-7), such as 2:4, 2:4.5, 2:5, 2:6 or 2:7. The graphite material and potassium manganate of the present invention are in a suitable mass ratio to obtain graphite with a suitable mesoporosity. If the amount of potassium manganate is too low or too high, the mesoporosity of the obtained graphite is too low or too high, which will be detrimental to the performance of the composite electrode material.
[0038] In some embodiments, the temperature of the first heat treatment is 1000-1200°C, including but not limited to 1000°C, 1050°C, 1080°C, 1100°C, 1120°C, 1150°C, 1180°C, 1200°C, etc., or any range between the two. The time of the first heat treatment is 3-6h, such as 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h, etc., or any range between the two. Suitable first heat treatment conditions can ensure the physical and chemical properties of mesoporous graphite.
[0039] In some embodiments, the mesoporous graphite has a mesoporosity of 50% to 70%, including but not limited to 50%, 52%, 55%, 56%, 58%, 60% or 70%, or any range between the two. The mesoporous graphite of the present invention has a suitable mesoporosity to ensure the silicon loading effect and the electrical properties of the silicon-carbon material, so as to facilitate the subsequent carbon nitride coating effect and improve the comprehensive electrical properties of the composite electrode material.
[0040] In some embodiments, after the first heat treatment, washing and drying are further performed to obtain mesoporous graphite. The washing is performed by acid washing, such as hydrochloric acid solution, followed by suction filtration to neutrality and vacuum drying to obtain mesoporous graphite.
[0041] In some embodiments, during the deposition of the gaseous silicon source on the mesoporous graphite, the deposition temperature is 400-800°C, including but not limited to 400°C, 450°C, 480°C, 500°C, 550°C, 600°C, 700°C or 800°C, or any range between the two. The deposition time is 1-15h, such as 1h, 2h, 4h, 8h, 9h, 10h, 11h, 12h, 13h, 14h or 15h, or any range between the two. The pressure is 0.01-10Kpa, such as 0.01Kpa, 0.05Kpa, 0.1Kpa, 1Kpa, 5Kpa or 10Kpa, etc. The flow rate of the gaseous silicon source is 0.5-2L / min, such as 0.5L / min, 0.8L / min, 1L / min, 1.5L / min or 2L / min, etc. In some embodiments, the gaseous silicon source includes at least one of trichloromethylsilane, dichlorodimethylsilane, tetraethoxysilane, methyltriethoxysilane, monosilane, disilane, and trichlorosilane. The suitable deposition conditions of the present invention can ensure the deposition effect of silicon and ensure better electrical properties of silicon-carbon materials.
[0042] In some embodiments, the titanium source alcohol solution includes titanium tetrachloride ethanol solution. The mass fraction of the titanium source alcohol solution is 8% to 12%, such as 8%, 9%, 10%, 11% or 12%, or any range between the two. The appropriate concentration of the titanium source alcohol solution is beneficial to its coating effect and forms a more uniform coating layer.
[0043] In some embodiments, the mass ratio of the titanium source alcohol solution and the porous silicon-carbon material is (2-4):1, such as 2:1, 2.5:1, 3:1, 3.5:1, 4:1, etc. The titanium source alcohol solution and the porous silicon-carbon material adopt a suitable mass ratio to ensure the formation of a uniform titanium nitride coating layer of suitable thickness. If the mass of the titanium source alcohol solution is too high and the coating layer is too thick, or the mass of the titanium source alcohol solution is too low and the coating layer is too thin, the electrochemical performance of the final composite electrode material will be reduced.
[0044] In some embodiments, the second heat treatment includes preheating and calcining. The preheating temperature is 400-550°C, such as 400°C, 420°C, 450°C, 480°C, 500°C, 520°C, 550°C, etc., or any range between the two, and the preheating time is 1-5h, such as 1h, 2h, 3h, 4h or 5h, etc. The calcining temperature is 1400-1600°C, such as 1400°C, 1420°C, 1450°C, 1480°C, 1500°C, 1520°C, 1550°C, 1580°C, 1600°C, etc., or any range between the two. The holding time is 3-7h, such as 3h, 3.5h, 4h, 5h, 6h or 7h, etc. The calcination is carried out under protective gas conditions, such as nitrogen, with a pressure of 0.08-0.12 MPa, such as 0.09 MPa, 0.1 MPa, 0.12 MPa, etc.
[0045] In a preferred embodiment, the method for preparing the composite electrode material comprises the following steps:
[0046] (a) artificial graphite and potassium manganate are mixed and loaded into a reaction container, the mass ratio of artificial graphite to potassium manganate is 2:(4-7), and heated to 1000-1200°C for reaction, and the reaction time is 3-7 hours. The reactant is washed with hydrochloric acid solution, then filtered to neutrality, and vacuum dried to obtain mesoporous graphite.
[0047] (b) adding mesoporous graphite into a fluidized bed reactor, introducing a silane / nitrogen mixed gas, the pressure in the reactor is 0.01-10 KPa, the flow rate of the gaseous silicon source is 0.5-2 L / min, reacting at 400-800° C. for 1-15 h, and obtaining a porous silicon-carbon material.
[0048] (c) Mix and stir the titanium tetrachloride ethanol solution (mass fraction of 8% to 15%) and the porous silicon-carbon material in a mass ratio of (2 to 4):1, and pre-calculate the mixed slurry at 400 to 550°C to remove moisture and other volatile substances. Then, in a nitrogen atmosphere, heat the pre-calcined mixture to 1400 to 1600°C, keep it for 3 to 7 hours, and press it at 0.08 to 0.12 MPa. After the reaction is completed, cool it naturally to obtain a composite electrode material, i.e., a titanium nitride-coated porous silicon-carbon material.
[0049] According to another aspect of the present invention, the present invention also relates to a composite electrode material prepared by the composite electrode material preparation method.
[0050] The composite electrode material of the present invention has a core of silicon-carbon material, and mesoporous graphite reserves space for silicon expansion to prevent the material from breaking during charging and lithium insertion. At the same time, the appropriate mesoporosity is conducive to lithium ion diffusion. The surface of the silicon-carbon material is coated with a titanium nitride coating layer, which has good lithium ion diffusion, few interface side reactions, and little change in interface impedance. After cycling, the material surface still has good lithium ion diffusion capacity.
[0051] According to another aspect of the present invention, the present invention also relates to an electrode sheet, comprising the composite electrode material prepared by the method for preparing the composite electrode material, or the composite electrode material mentioned above.
[0052] In some embodiments, the electrode sheet includes a negative electrode current collector and a negative electrode active layer located on the surface of the negative electrode current collector, and the negative electrode active layer includes the above-mentioned composite electrode material, a conductive agent and a binder.
[0053] According to another aspect of the present invention, the present invention also relates to a battery, comprising the above-mentioned electrode sheet.
[0054] The battery of the present invention has excellent lithium ion diffusion capacity, low expansion when fully charged, and good cycle performance.
[0055] According to another aspect of the present invention, the present invention also relates to an electric device, comprising the above-mentioned battery. The electric device includes an electric car and the like.
[0056] The following is further explained in conjunction with specific embodiments and comparative examples.
[0057] Example 1
[0058] A method for preparing a composite electrode material comprises the following steps:
[0059] (1) Artificial graphite and K2MnO4 were mixed and placed in a reaction vessel (mass ratio of 2:5), heated to 1100°C for reaction, and the reaction time was 5 hours. The reactant was washed with hydrochloric acid solution, then filtered to neutrality, and vacuum dried to obtain mesoporous graphite.
[0060] (2) The mesoporous graphite was added into a fluidized bed reactor, and a disilane / nitrogen mixed gas was introduced, the disilane flow rate was 2 L / min, the volume ratio of disilane to nitrogen was 1:1, the pressure in the reactor was 5 KPa, and the reaction was carried out at 500 °C for 12 h to obtain a porous silicon-carbon material.
[0061] (3) Titanium tetrachloride ethanol solution (mass fraction of 10%) and porous silicon carbon material are mixed and stirred in a mass ratio of 3:1, and the mixed slurry is pre-calcined at 500°C to remove moisture and other volatile substances. Then, in a nitrogen atmosphere, the pre-calcined mixture is heated to 1500°C, kept at this temperature for 5 hours, and the pressure is 0.1MPa. After the reaction is completed, it is naturally cooled to obtain a composite electrode material, i.e., titanium nitride-coated porous silicon carbon material.
[0062] Example 2
[0063] A method for preparing a composite electrode material comprises the following steps:
[0064] (1) Artificial graphite and K2MnO4 were mixed and placed in a reaction vessel (mass ratio of 2:6), heated to 1150°C for reaction, and the reaction time was 4 hours. The reactant was washed with hydrochloric acid solution, then filtered to neutrality, and vacuum dried to obtain mesoporous graphite.
[0065] (2) The mesoporous graphite was added into a fluidized bed reactor, and a disilane / nitrogen mixed gas was introduced, the disilane flow rate was 2 L / min, the volume ratio of disilane to nitrogen was 1:1, the pressure in the reactor was 5 KPa, and the reaction was carried out at 550° C. for 10 h to obtain a porous silicon-carbon material.
[0066] (3) Titanium tetrachloride ethanol solution (mass fraction of 10%) and porous silicon-carbon material were mixed and stirred at a mass ratio of 3.5:1, and the mixed slurry was pre-calcined at 470°C to remove moisture and other volatile substances. Then, in a nitrogen atmosphere, the pre-calcined mixture was heated to 1540°C, kept at this temperature for 4 hours, and the pressure was 0.1MPa. After the reaction was completed, it was naturally cooled to obtain a composite electrode material, i.e., titanium nitride-coated porous silicon-carbon material.
[0067] Example 3
[0068] A method for preparing a composite electrode material comprises the following steps:
[0069] (1) Artificial graphite and K2MnO4 were mixed and placed in a reaction vessel (mass ratio of 2:4), heated to 1200°C for reaction, and the reaction time was 3 hours. The reactant was washed with hydrochloric acid solution, then filtered to neutrality, and vacuum dried to obtain mesoporous graphite.
[0070] (2) The mesoporous graphite was added into a fluidized bed reactor, and a monosilane / nitrogen mixed gas was introduced, the monosilane flow rate was 1.5 L / min, the volume ratio of monosilane to nitrogen was 1:1, the pressure in the reactor was 0.01 KPa, and the reaction was carried out at 400°C for 15 hours to obtain a porous silicon-carbon material.
[0071] (3) Titanium tetrachloride ethanol solution (mass fraction of 10%) and porous silicon carbon material were mixed and stirred in a mass ratio of 4:1, and the mixed slurry was pre-calcined at 550°C to remove moisture and other volatile substances. Then, in a nitrogen atmosphere, the pre-calcined mixture was heated to 1400°C, kept at this temperature for 7 hours, and the pressure was 0.08MPa. After the reaction was completed, it was naturally cooled to obtain a composite electrode material, i.e., titanium nitride-coated porous silicon carbon material.
[0072] Example 4
[0073] A method for preparing a composite electrode material comprises the following steps:
[0074] (1) Artificial graphite and K2MnO4 were mixed and placed in a reaction vessel (mass ratio of 2:7), heated to 1000°C for reaction, and the reaction time was 6 hours. The reactant was washed with hydrochloric acid solution, then filtered to neutrality, and vacuum dried to obtain mesoporous graphite.
[0075] (2) The mesoporous graphite was added into a fluidized bed reactor, and a monosilane / nitrogen mixed gas was introduced, the monosilane flow rate was 2 L / min, the volume ratio of monosilane to nitrogen was 1:1, the pressure in the reactor was 10 KPa, and the reaction was carried out at 600 ° C for 8 h to obtain a porous silicon-carbon material.
[0076] (3) Titanium tetrachloride ethanol solution (mass fraction of 10%) and porous silicon carbon material are mixed and stirred in a mass ratio of 2:1, and the mixed slurry is pre-calcined at 400°C to remove moisture and other volatile substances. Then, in a nitrogen atmosphere, the pre-calcined mixture is heated to 1600°C, kept at this temperature for 3 hours, and the pressure is 0.12MPa. After the reaction is completed, it is naturally cooled to obtain a composite electrode material, i.e., titanium nitride-coated porous silicon carbon material.
[0077] Example 5
[0078] A method for preparing a composite electrode material, which differs from Example 1 in that:
[0079] The mass ratio of artificial graphite to K2MnO4 is 1:6.
[0080] Example 6
[0081] A method for preparing a composite electrode material, which differs from Example 1 in that:
[0082] The mass ratio of artificial graphite to K2MnO4 is 6:5.
[0083] Example 7
[0084] A method for preparing a composite electrode material, which differs from Example 1 in that:
[0085] The mass ratio of the titanium tetrachloride ethanol solution to the porous silicon carbon material is 6:1.
[0086] Comparative Example 1
[0087] A method for preparing a composite electrode material comprises the following steps:
[0088] The porous silicon-carbon material was obtained by following steps (1) and (2) of Example 1.
[0089] Comparative Example 2
[0090] A method for preparing a composite electrode material, which differs from Example 1 in that:
[0091] The porous silicon-carbon material was obtained by performing operations according to steps (1) and (2) of Example 1. The porous silicon-carbon material was kept in the fluidized bed reactor, acetylene gas was introduced, and the material was pyrolyzed at 600° C. for 5 h to obtain a carbon-coated porous silicon-carbon material.
[0092] Experimental example
[0093] The composite electrode materials prepared in the above-mentioned embodiments and comparative examples are mixed and stirred evenly with the binder polyacrylic acid, conductive carbon black and dispersant sodium carboxymethyl cellulose. The mass ratio of the composite electrode material, polyacrylic acid, conductive carbon black and sodium carboxymethyl cellulose is 95:1:2:2. Each material is mixed with water to obtain a negative electrode slurry. The negative electrode slurry is then coated on a copper foil and dried, and the negative electrode sheet is obtained by cutting. In the electrolyte used, LiPF6 is the electrolyte with a concentration of 1.5 mol / L, and the solvent is a mixture of EC and DEC in a volume ratio of 1:1; the metal lithium sheet is the counter electrode, and the diaphragm uses a polypropylene (PP) film. The button cell is assembled in a glove box filled with argon. The performance test of the battery is as follows:
[0094] 1. Diffusion coefficient test
[0095] Assemble the negative electrode sheet and the lithium sheet and discharge at 0.1C. The single-step discharge time is 2 minutes. Let it stand for 30 minutes. Repeat the above steps until the voltage is less than 0.005V. Record the voltage at each step and calculate the lithium ion diffusion coefficient.
[0096] 2. Fully charged expansion
[0097] Test the initial thickness of the negative electrode sheet D0, assemble the negative electrode sheet and the lithium sheet, discharge at 0.1C until the voltage is <0.005V, let it stand for 30min, discharge at 0.02C until the voltage is <0.005V, disassemble and test the thickness of the negative electrode sheet D1, the expansion rate = (D1-D0) / (D0-D 铜箔 ).
[0098] 3. Cycle performance test
[0099] The prepared button battery was subjected to cyclic charge and discharge at a rate of 0.1C with a voltage range of 0.005-1.5V, and the capacity retention rate of the battery was recorded after 600 cycles.
[0100] The test results are shown in Table 1.
[0101] Table 1 Test results
[0102]
[0103] It can be seen from Table 1 that the battery prepared from the composite electrode material obtained by the methods of Examples 1 to 4 of the present invention has a suitable diffusion coefficient, a low expansion coefficient, a high initial efficiency, and a high capacity retention rate.
[0104] By comparing Example 1 with Examples 5 to 6, it can be seen that Example 1 of the present invention uses K2MnO4 to etch artificial graphite, and the appropriate ratio can make the material have a lower expansion rate, a suitable mesoporosity and a better lithium ion diffusion capacity. If the proportion of K2MnO4 is too low, the obtained material has fewer mesopores, silicon is difficult to deposit, and the volume expansion of silicon cannot be effectively buffered; if the proportion of K2MnO4 is too high, the initial efficiency of the obtained material is low.
[0105] By comparing Example 1, Example 7, and Comparative Example 1, it can be seen that the material of Comparative Example 1 is not coated with TiN, and the electrolyte and material side reactions cannot be prevented, the capacity decays quickly, the cycle performance is poor, and the lithium ion diffusion coefficient decreases significantly due to the large interface impedance after the cycle. Too much TiN coating in Example 7 will also reduce the lithium ion transmission performance.
[0106] By comparing Example 1 and Comparative Example 2, it can be seen that the TiN-coated porous silicon-carbon material in Example 1 has a significant effect on reducing material side reactions and maintaining lithium ion diffusivity after cycling compared to the carbon-coated material in Comparative Example 2.
[0107] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a composite electrode material, characterized in that: The following steps are involved: Performing a first heat treatment on the graphite material and potassium manganate to obtain mesoporous graphite, and depositing a gaseous silicon source on the mesoporous graphite to obtain a porous silicon-carbon material; The mixed system of the porous silicon-carbon material and the titanium source alcohol solution is subjected to a second heat treatment to obtain a composite electrode material.
2. The method for preparing a composite electrode material according to claim 1, characterized in that: The mass ratio of the graphite material to potassium manganate is 2:(4-7); And / or, the temperature of the first heat treatment is 1000-1200° C., and the time of the first heat treatment is 3-6 hours; And / or, the mesoporous graphite has a mesoporosity of 50% to 70%; And / or, after the first heat treatment, washing and drying are further included to obtain the mesoporous graphite.
3. The method for preparing a composite electrode material according to claim 1, characterized in that: In the process of depositing the gaseous silicon source on the mesoporous graphite, the deposition temperature is 400-800° C., the deposition time is 1-15 hours, the pressure is 0.01-10 Kpa, and the flow rate of the gaseous silicon source is 0.5-2 L / min.
4. The method for preparing a composite electrode material according to claim 1, characterized in that: The titanium source alcohol solution includes titanium tetrachloride ethanol solution; And / or, the mass fraction of the titanium source alcohol solution is 8% to 12%; And / or, the mass ratio of the titanium source alcohol solution to the porous silicon-carbon material is (2-4):
1.
5. The method for preparing a composite electrode material according to claim 1, characterized in that: The second heat treatment includes preheating and calcining.
6. The method for preparing a composite electrode material according to claim 5, characterized in that: The preheating temperature is 400-550°C, and the preheating time is 1-5h; And / or, the calcination temperature is 1400-1600° C., and the holding time is 3-7 hours; And / or, the calcination is carried out under protective gas conditions with a pressure of 0.08 to 0.12 MPa.
7. A composite electrode material, characterized in that: The composite electrode material is prepared by the method for preparing the composite electrode material according to any one of claims 1 to 6.
8. An electrode sheet, characterized in that: A composite electrode material prepared by the method for preparing a composite electrode material according to any one of claims 1 to 6, or a composite electrode material according to claim 7.
9. A battery, characterized in that: Comprising the electrode sheet as claimed in claim 8.
10. An electrical device, characterized in that: A battery comprising the battery of claim 9.
Citation Information
Patent Citations
Silicon-carbon negative electrode material, preparation method and lithium ion battery
CN110739455A
Silicon carbon material as well as preparation method and application thereof
CN116995196A
Silicon carbon material, preparation method thereof and lithium ion battery
CN116995197A
Ternary positive electrode material coated with nitride / graphitized carbon nanosheets and preparation method thereof
US20240097116A1
Preparation method for porous graphite-doped and carbon-coated lithium titanate negative electrode material
WO2016188130A1